A teachers' perspective on the influence of singing activity on expression of children's emotion / Muhammad Syamim Haikal Sa'aid - Sa'aid, Muhammad Syamim Haikal (2022)
The most important question in the psychology of music is how music affects an individual's emotional experience, which has been the subject of extensive research. However, the outcome appeared from a variety of perspectives, and at times it devolved into endless debates and arguments. When it comes to music, every individual's emotional state will have a different impact on how it is influenced, depending on whether the emotion is expressed through listening, playing, or participating in musical activities. Musical activities such as singing in preschool are one of the examples that can be used to demonstrate how music can influence an individual's emotional responses. The purpose of this study is to gain an understanding of teachers' perspectives on the influence of singing activities on the expression of children's emotions, because they are the ones who organise the activities and are able to observe the children's participation. The qualitative study was conducted by interviewing 7 preschool teachers who are teaching in Shah Alam, Selangor to identify their perspectives on the influence of singing activity on the expression of children's emotion. It is also to be noted that the qualitative approach is relevant to this study in order to discover in depth about the teachers' perspective on the influence of singing activity on expression of children's emotion. Data was collected by using an audio recorder and when the interview has been done, all the recorded data will be transcribed. The research findings of this study can support and contribute that music can influence human's emotion in general. These research findings will then be advantageous to the music researcher and psychologist as it gives them research content in the study of music and emotion.